Constraining the Magnitude of Climate Extremes From Time‐Varying Instellation on a Circumbinary Terrestrial Planet. Issue 12 (3rd December 2019) - Haqq‐Misra, Jacob; Wolf, Eric T.; Welsh, William F.; Kopparapu, Ravi Kumar; Kostov, Veselin; Kane, Stephen R.
Abstract: Planets that revolve around a binary pair of stars are known as circumbinary planets. The orbital motion of the stars around their center of mass causes a periodic variation in the total instellation incident upon a circumbinary planet. This study uses both an analytic and numerical energy balance model to calculate the extent to which this effect can drive changes in surface temperature on circumbinary terrestrial planets. We show that the amplitude of the temperature variation is largely constrained by the effective heat capacity, which corresponds to the ocean‐to‐land ratio on the planet. Planets with large ocean fractions should experience only modest warming and cooling of only a few degrees, which suggests that habitability cannot be precluded for such circumbinary planets. Planets with large land fractions that experience extreme periodic forcing could be prone to changes in temperature of tens of degrees or more, which could drive more extreme climate changes that inhibit continuously habitable conditions. Key Points: We calculate the maximum extent of temperature variation for a circumbinary planet using analytic and numerical energy balance models Planets with large ocean coverage experience only a few degrees of temperature variation, which would not preclude habitability Planets with large land coverage may experience tens of degrees or more in temperature variation, which could cause extreme climate change